X-ray diffraction and TGA kinetic analyses for chemical looping combustion applications - Tijani, M.M. (Elsevier Inc., 2018)
Synthesis and characterization of supported metal-based oxygen carriers were carried out to provide information related to the use of oxygen carriers for chemical looping combustion processes. The Cu, Co, Fe, Ni metals supported with Al2O3, CeO2, TiO2, ZrO2 were prepared using the wetness impregnation technique. Then, the X-ray Diffraction (XRD) characterization of oxidized and reduced samples was obtained and presented. The kinetic analysis using Thermogravimetric analyzer (TGA) of the synthesized samples was conducted. The kinetics of reduction reaction of all samples were estimated and explained. Â© 2018